2009
DOI: 10.1175/2009jpo4016.1
|View full text |Cite
|
Sign up to set email alerts
|

Axial Wind Effects on Stratification and Longitudinal Salt Transport in an Idealized, Partially Mixed Estuary*

Abstract: A 3D hydrodynamic model [Regional Ocean Model System (ROMS)] is used to investigate how axial wind influences stratification and to explore the associated longitudinal salt transport in partially mixed estuaries. The model is configured to represent a straight estuarine channel connecting to a shelf sea. The results confirm that wind straining of the along-channel salinity gradient exerts an important control on stratification. Two governing parameters are identified: the Wedderburn number (W) defined as the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
121
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 45 publications
9
121
0
Order By: Relevance
“…For example, Valle-Levinson et al (2004) showed, from measurements, how the balance between wind stress and barotropic pressure gradients justifies the vertical integrated dynamics for a specific strait in the Chilean Sea. In order to investigate the wind effects on stratification of waters in the Klaipėda Strait and type of flow regime, two governing dimensionless parameters are identified: the Wedderburn number (W ), defined as the ratio of wind stress to axial baroclinic pressure gradient force, and the ratio of the buoyancy layer depth to water depth (h b /H ) (Chen and Sanford, 2009). The Wedderburn number (Monismith, 1986) describes the relative importance between the wind-driven circulation and the baroclinic pressure gradient along the strait: where τ wx is the along-strait wind stress (positive up-strait, e.g., towards the lagoon), L is the length of the strait (14 km), ρ is the density change over L, g is the gravitational acceleration, and H is the averaged depth of the strait (11 m).…”
Section: The Water Flow Dynamics In Klaipėda Straitmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Valle-Levinson et al (2004) showed, from measurements, how the balance between wind stress and barotropic pressure gradients justifies the vertical integrated dynamics for a specific strait in the Chilean Sea. In order to investigate the wind effects on stratification of waters in the Klaipėda Strait and type of flow regime, two governing dimensionless parameters are identified: the Wedderburn number (W ), defined as the ratio of wind stress to axial baroclinic pressure gradient force, and the ratio of the buoyancy layer depth to water depth (h b /H ) (Chen and Sanford, 2009). The Wedderburn number (Monismith, 1986) describes the relative importance between the wind-driven circulation and the baroclinic pressure gradient along the strait: where τ wx is the along-strait wind stress (positive up-strait, e.g., towards the lagoon), L is the length of the strait (14 km), ρ is the density change over L, g is the gravitational acceleration, and H is the averaged depth of the strait (11 m).…”
Section: The Water Flow Dynamics In Klaipėda Straitmentioning
confidence: 99%
“…Previous investigations of the lagoons have mainly focused on tidal-and winddriven exchanges across the inlets (Stommel and Farmer, 1952;Wong, 1991;Geyer and Signell, 1992;Churchill et al, 1999;Hench et al, 2002;. However, more and more attention in recent years is paid to circulation dynamics and salt balance inside the estuarine lagoons (Reyes-Hernandez and Valle-Levinson, 2010;Chen and Sanford, 2009;Jia and Li, 2012a, b;Kim and Park, 2012;Li and Li, 2012). Estuarine lagoons with complex interactions between biotic and abiotic components depend on the water exchange between the lagoon and the sea.…”
Section: Introductionmentioning
confidence: 99%
“…which is much smaller than the critical value of ~1 (0.85 in Chen and Sanford, 2009) and suggests that the wind straining effect dominates over the wind mixing. The Wedderburn numbers for the mean down-estuary (N, NE) winds are 0.14 and 0.08, respectively, again indicating that the wind straining dominates.…”
mentioning
confidence: 78%
“…The down-estuary wind can enhance stratification and estuarine circulation via wind straining, and can also simultaneously increase vertical mixing via wind mixing; therefore its effect on salt transport reflects the competition between these two components. However, the up-estuary wind increases vertical mixing and decreases estuarine circulation, consequently reducing the salt intrusion (Chen and Sanford, 2009;Jia and Li, 2012).…”
mentioning
confidence: 99%
“…First, they drive a two-layer circulation that opposes gravitational circulation, in which surface currents flow into the estuary in the same direction as the wind and near-bottom currents return water to the ocean. Additionally, the water column is mixed through direct wind mixing, where turbulence generated at the air-sea interface is transferred down through the water column [54]. During all tidal cycles sampled, the dominant salt transport term was F 0 ( Table 1), indicating that fluxes of salt were primarily driven by a combination of freshwater discharge through the HNC and wind-driven changes in storage over the course of the tidal cycle.…”
Section: Tidal Cycle Salinity and Velocity Surveys And Salt Flux Decomentioning
confidence: 99%